Relación entre la distopia genital y la incontinencia urinaria, en el consultorio de Ginecología del Hospital II - 2 Tarapoto 2019 - Incio Huamanchumo, Jose Xavier (2021)
Objective: To analyze the relationship between genital dystopia and urinary incontinence (UI) in patients attended at the gynecology department of the Hospital II-2 Tarapoto, 2019. Method: An analytical, retrospective, cross-sectional, retrospective observational study was carried out, made up of 100 women at the gynecology department of Hospital II-2 Tarapoto 2019; in whom the gynecological-obstetric clinical history was reviewed in search of urinary incontinence and/or genital dystopia. The data were analyzed in the SPSS version 25 program, determining the association by calculating the Odds ratio and significance by Pearson's Chi-square. Results: Urinary incontinence frequency was 81%, where the average age was 63 years. 91.4% of women with UI presented dystopia (OR: 14.54, 95%CI: 4.39-48.06), grade 3 was the most frequent grade associated with incontinence (OR: 7.51, p=0.004) and both Cystocele and Hystocele were the types of dystopia associated with UI (OR: 4.46 and OR: 3.86, respectively). Likewise, eutocic delivery (OR: 3.89, p=0.008) and being multiparous (OR: 4.48, p=0.017), were factors associated with UI. Conclusion: genital dystopia and urinary incontinence present an association relationship in patients attended at the gynecology department of Hospital II-2 Tarapoto, 2019.